2002
DOI: 10.1093/emboj/cdf489
|View full text |Cite
|
Sign up to set email alerts
|

The disulfide bond isomerase DsbC is activated by an immunoglobulin-fold thiol oxidoreductase: crystal structure of the DsbC-DsbDalpha complex

Abstract: The Escherichia coli disul®de bond isomerase DsbC rearranges incorrect disul®de bonds during oxidative protein folding. It is speci®cally activated by the periplasmic N-terminal domain (DsbDa) of the transmembrane electron transporter DsbD. An intermediate of the electron transport reaction was trapped, yielding a covalent DsbC±DsbDa complex. The 2.3 A Ê crystal structure of the complex shows for the ®rst time the speci®c interactions between two thiol oxidoreductases. DsbDa is a novel thiol oxidoreductase wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
151
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 59 publications
6
151
0
Order By: Relevance
“…DsbD is composed of three domains: an N-terminal immunoglobulin-like domain (␣), a central hydrophobic core (␤) with eight transmembrane segments (TM segments), and a Cterminal periplasmic domain (␥), which appears to be a member of the thioredoxin superfamily (12)(13)(14)(15)(16)(17) (Fig. 1A).…”
mentioning
confidence: 99%
“…DsbD is composed of three domains: an N-terminal immunoglobulin-like domain (␣), a central hydrophobic core (␤) with eight transmembrane segments (TM segments), and a Cterminal periplasmic domain (␥), which appears to be a member of the thioredoxin superfamily (12)(13)(14)(15)(16)(17) (Fig. 1A).…”
mentioning
confidence: 99%
“…We found that 11/88 (12.5%) cases could be explained by such asymmetric multibinding. Figure 4b shows the 2:1 complex of the Escherichia coli disulphide bond isomerase with the N-terminal domain of the transmembrane electron transporter DsbD 42 . Here, a single DsbD chain is able to use two dissimilar surfaces to bind very similar regions containing the active site on each DsbC molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Here, a single DsbD chain is able to use two dissimilar surfaces to bind very similar regions containing the active site on each DsbC molecule. It has been suggested that this asymmetric binding allows DsbD to distinguish oxidized from reduced DsbC 42 .…”
Section: Resultsmentioning
confidence: 99%
“…28 However, Trx-fold proteins also undergo direct dithiol/disulfide exchange with other Trx-fold proteins. 29,30 Therefore, the interaction between two CXXC motifs at the amino termini of helices with the aid of the neighboring cis-proline as observed in RnQSOX1 may be relevant to other biological dithiol/disulfide exchange events.…”
Section: Discussionmentioning
confidence: 99%
“…The X-ray crystal structure model contained 498 amino acid residues in monomer A, 91 waters, and the cofactor FAD. Amino acid residues missing from the model (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(279)(280)(281)(282)(283)(284)(285)(286)(287)(288)(289)(290), and 548-550) were added using Discovery Studio 3.5 (Accelrys), prior to commencing simulations. Residues 25-36 and 548-550 were added in an extended conformation and subjected to geometry minimization and MD simulations, whereas the remainder of the enzyme was kept fixed.…”
Section: Model Construction For Simulationsmentioning
confidence: 99%